2009
DOI: 10.1021/jf901020h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Major Phenolic Constituents and in Vitro Antioxidant Activity of Diverse Kudingcha Genotypes from Ilex kudingcha, Ilex cornuta, and Ligustrum robustum

Abstract: A total of seven Kudingcha genotypes from three plant species (Ilex kudingcha, Ilex cornuta, and Ligustrum robustum) with different geographic origins in China were investigated for their major phenolic compounds, individual and total phenolics contents, and in vitro antioxidant properties (ABTS, DPPH, FRAP, and OH assays). LC-PDA-APCI-MS analysis showed that Kudingcha genotypes from Ilex and Ligustrum had entirely different phenolic profiles. Major phenolics in Kudingcha genotypes from two Ilex species were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 27 publications
(79 reference statements)
7
79
0
Order By: Relevance
“…The IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum in the DPPH assay were 0.48, 0.94, 1.38, 1.47, and 2.06 mg/ml, respectively. The results obtained from the DPPH assay is similar to recent reports of other Ligustrum species, including L. lucidum and L. robustum (Chen, Wong, Leung, He, & Huang, 2002;Katsube et al, 2004;Nagy et al, 2006;She, Wang, Zeng, Yang, & Zhang, 2008;Zhu et al, 2009). For the TEAC assay, the IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum were 0.21, 0.24, 0.37, 0.52, and 1.40 mg/ml, respectively.…”
Section: Antioxidant and Radical-scavenging Activity Of Ligustrum Leavessupporting
confidence: 86%
See 2 more Smart Citations
“…The IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum in the DPPH assay were 0.48, 0.94, 1.38, 1.47, and 2.06 mg/ml, respectively. The results obtained from the DPPH assay is similar to recent reports of other Ligustrum species, including L. lucidum and L. robustum (Chen, Wong, Leung, He, & Huang, 2002;Katsube et al, 2004;Nagy et al, 2006;She, Wang, Zeng, Yang, & Zhang, 2008;Zhu et al, 2009). For the TEAC assay, the IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum were 0.21, 0.24, 0.37, 0.52, and 1.40 mg/ml, respectively.…”
Section: Antioxidant and Radical-scavenging Activity Of Ligustrum Leavessupporting
confidence: 86%
“…The FRAP assay described by Zhu et al (2009) was used with some modifications. Briefly, 25 l of sample solution or Trolox standards was mixed with 25 l of freshly prepared FRAP reagent, which consisted of 10 mM TPTZ solution in 40 mM HCl, 20 mM FeCl 3 , and 50 mM acetate buffer (pH 3.6).…”
Section: Frap Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…12,[16][17][18] Since oxidative stress plays a key role in Ab-induced neurotoxicity, 4,42 antioxidants have been studied to exploit their neuroprotective effects in AD models. CQAs have been reported to protect neurons against Ab-promoted neuronal cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, the antioxidant properties and phenolic compounds of I. latifolia have been evaluated. 11,12 Due to the antioxidant activity of I. latifolia, neuroprotective effects of this plant have also been examined. 13 In a previous study, we demonstrated that the antioxidative and anti-inflammatory effects of I. latifolia provided protection against apoptotic neuronal death associated with transient focal ischemia-induced brain damage.…”
Section: Introduction Amentioning
confidence: 99%